2012
DOI: 10.1073/pnas.1121567109
|View full text |Cite
|
Sign up to set email alerts
|

PK4, a eukaryotic initiation factor 2α(eIF2α) kinase, is essential for the development of the erythrocytic cycle of Plasmodium

Abstract: In response to environmental stresses, the mammalian serine threonine kinases PERK, GCN2, HRI, and PKR phosphorylate the regulatory serine 51 of the eukaryotic translation initiation factor 2α (eIF2α) to inhibit global protein synthesis. Plasmodium , the protozoan that causes malaria, expresses three eIF2α kinases: IK1, IK2, and PK4. Like GCN2, IK1 regulates stress response to amino acid starvation. IK2 inhibits development of malaria sporozoites present in the mosquito salivary glands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
128
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 37 publications
6
128
0
1
Order By: Relevance
“…Moreover, it has been reported that phosphorylation of eIF2␣ in Toxoplasma gondii is critical for the resistance of the parasite to external stress outside its host; inhibition of this phosphorylation significantly delays the development of acute toxoplasmosis in vivo (9). In Plasmodium, phosphorylation of PfeIF2␣ is essential for the development of the erythrocytic cycle (10), and nutritional stress-induced eIF2␣ phosphorylation in Trypanosoma cruzi regulates metacyclogenesis (11). In Leishmania infantum, phosphorylation of eIF2␣ has been interpreted with the differentiation of the parasite under concomitant exposure to high temperature and acidic pH (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that phosphorylation of eIF2␣ in Toxoplasma gondii is critical for the resistance of the parasite to external stress outside its host; inhibition of this phosphorylation significantly delays the development of acute toxoplasmosis in vivo (9). In Plasmodium, phosphorylation of PfeIF2␣ is essential for the development of the erythrocytic cycle (10), and nutritional stress-induced eIF2␣ phosphorylation in Trypanosoma cruzi regulates metacyclogenesis (11). In Leishmania infantum, phosphorylation of eIF2␣ has been interpreted with the differentiation of the parasite under concomitant exposure to high temperature and acidic pH (12).…”
mentioning
confidence: 99%
“…In Plasmodium, three eIF2␣ serine-threonine kinases, eIK1, eIK2, and PK4, have been identified with stage-specific expression (14), of which PK4 mediates translational repression in schizonts and is essential for the erythrocytic cycle in Plasmodium falciparum (10). Toxoplasma brucei TbeIF2K1 and TbeIF2K2, the first one of which is of the GCN2 type (15), and Toxoplasma gondii PERK-type TgIF2K-A and TgIF2K-B kinases have been reported in relation to the development of latent cysts under stress (8).…”
mentioning
confidence: 99%
“…RNA-binding proteins (Puf proteins) that repress translation by binding to the mRNA 3= untranslated region are specifically upregulated in gametocytes (Puf1 and Puf2) (27,28) and sporozoites (Puf2) (46,47). The phosphorylation of eIF2␣ in salivary gland sporozoites, mature schizonts, and gametocytes induces translational repression and storage of untranslated mRNAs as stress granules (42,52). Plasmodium sporozoites maintain infectivity for days in the salivary glands (69,70).…”
Section: Translational Control In Plasmodium Sexual Stagesmentioning
confidence: 99%
“…One of them, PfeIK2, controls latency in sporozoite development in the mosquito (17). Another, PfPK4, is involved in intraerythrocytic schizogony (18). The third, PfeIK1, recently has been confirmed as the amino acid-sensing GCN2 ortholog, active in the blood stages of the parasite and able to phosphorylate eIF2α in response to amino acid starvation (15).…”
mentioning
confidence: 99%